Electronic and optical properties of functionalized carbon chains with the localized Hartree-Fock and conventional Kohn-Sham methods - Weimer, Martin; Hieringer, Wolfgang; Della Sala, Fabio; Görling, Andreas (Chemical Physics, 2005)
The electronic and optical properties of extended functionalized carbyne chains, polyynes and cumulenes, are investigated with the localized Hartree-Fock method, with conventional Kohn-Sham methods, and with the Hartree-Fock method. It is found that even for very long polyynes the carbon-carbon bond lengths within a polyyne alternate while for long cumulenes no carbon-carbon bond length alternation occurs. Polyynes exhibit a finite HOMO-LUMO gap even if they become very long while cumulenes are found to become metallic in the limit of long chain lengths. The geometry and the electro-optical properties of polyynes cannot be influenced significantly by simple sp-σ-bonded end groups. The optically active Σ←X Σ electronic transition in polyynes is investigated by time-dependent density-functional theory (TDDFT). The known systematic underestimation of excitation energies in large chain-like systems by TDDFT methods is also found for the systems considered here. Deficiencies in the commonly used exchange-correlation kernels are identified as the main source of this shortcoming of TDDFT methods. Unphysical Coulomb self-interactions present in conventional Kohn-Sham potentials seem to not contribute significantly to the problem. © 2004 Elsevier B.V. All rights reserved.